Effects of antiepileptic drugs on hippocampal neurons coupled to micro-electrode arrays - Colombi, Ilaria; Mahajani, Sameehan; Frega, Monica; Gasparini, Laura; Chiappalone, Michela (Frontiers in Neuroengineering, 2013)
Hippocampal networks exhibit spontaneous electrophysiological activity that can be modulated by pharmacological manipulation and can be monitored over time using Micro-Electrode Arrays (MEAs), devices composed by a glass substrate and metal electrodes. The typical mode of activity of these dissociated cultures is the network-wide bursting pattern, which, if properly chemically modulated, can recall the ictal events of the epileptic phenotypes and is well-suited to study the effects of antiepileptic compounds. In this paper, we analyzed the changes induced by Carbamazepine (CBZ) and Valproate (VPA) on mature networks of hippocampal neurons in ‘control’ condition (i.e. in the culturing medium) and upon treatment with the pro-convulsant bicuculline (BIC). We found that, in both control and BIC - treated networks, high doses (100 µM – 1mM) of CBZ almost completely suppressed the spiking and bursting activity of hippocampal neurons. On the contrary, VPA never completely abolish the electrophysiological activity in both experimental designs. Interestingly, VPA cultures pre-treated with BIC showed dual effects. In fact, in some cultures, at low VPA concentrations (100 nM-1 µM), we observed decreased firing/bursting levels, which returned to values comparable to BIC-evoked activity at high VPA concentrations (100 µM – 1mM). In other cultures, VPA reduced BIC-evoked activity in a concentration-independent manner. In conclusion, our study demonstrates that MEA-coupled hippocampal networks are responsive to chemical manipulations and, upon proper pharmacological modulation, might provide model systems to detect acute pharmacological effects of antiepileptic drugs.